If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -13 + 5x = 12 Solving -13 + 5x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + 5x = 12 + 13 Combine like terms: -13 + 13 = 0 0 + 5x = 12 + 13 5x = 12 + 13 Combine like terms: 12 + 13 = 25 5x = 25 Divide each side by '5'. x = 5 Simplifying x = 5
| 1/(14-3x)=2/(5x+4) | | 0.7t=0.3+0.9t | | 2p+5r=a | | 3(5-2r)-2(-3r+1)= | | 10x-(4x-8)=50 | | 4(5-4k)=-60 | | 8-34= | | 4+6/x | | 14=5x+2 | | -3(x-8)=18 | | (6x+20)+(2x+4)=164 | | (3x+2)/4=16-2x | | Y+3/r=r^2 | | 3,823=5/100 | | -2(7y-5)=-14y-23 | | -18-11r=2b | | 1/4+1/5+1/2+150 | | 2(3z+1)-8=48 | | 8-5(z+2)=-2(5z-2)-2 | | 2x+11+x+7=18 | | n+3.1n-4.7=3.6(n-4.5) | | 0.168x=0.2x+0.667 | | 3(x+3)-6x=2(4-2x) | | -145=7r+2(7r+1) | | 6(x-5)=4(2x-1) | | 3x+9=44-2y | | M*0= | | -2.7u+5.3=-1.4u-2.5 | | 2/3/87 | | 3w-(6+w)=12 | | 17=2k+8+k | | 90(2/5) |